Sosialisasi Pemberdayaan Manajemen UMKM dan Strategi Pemasaran Produk dalam Meningkatkan Penjualan Usaha - Dian Rachmawati Afandi; Indra Permana; Muhamad Syahwildan; Arif Widodo Nugroho; Daspar Daspar (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesian people are increasingly creative and innovative in making new recipes to add to their daily food needs, besides that they are also creative in making snacks typical of their region. Currently, according to young people and parents, snacks are much loved, besides that with a distinctive taste from the West Java region in the city of Bandung which is familiar to be heard or felt by people who mostly like snacks with a spicy taste, namely